Oral and Verbal Praxis in Impaired Language Learners. Issue 1 (February 2022) - Narayanan, Swapna; Vijayan, Kavya; Vastare Guruprasad, Mekhala; Prabhu P, Prashanth; Barman, Animesh
In the context of language descriptions, the terms oral and verbal praxis refer to volitional movements for performing oral gestures and movements for speech. These movements involve programming articulators and rapid sequences of muscle firings that are required for speech sound productions. A growing body of research has highlighted the links between oral motor kinematics and language production skills in both typically developing (TD) children and children with developmental language disorders, including Specific Language Impairment (SLI). Yet, there have been limited attempts to assess the link between non-linguistic and linguistic development. In the present study, we investigated oral and verbal praxis behaviors in children with SLI. Fifteen children with SLI formed a clinical group and 15 children with typical development who were matched to the clinical group for chronological age, gender, and socio-economic status formed the TD group. We assessed participants in both groups for their language abilities with age-appropriate standardized language tests. To investigate oral and verbal praxis behaviors, we administered the Assessment Protocol for Oral Motor, Oral Praxis and Verbal Praxis Skills to the two groups. We used the non-parametric Mann–Whitney U test to compare the two groups with respect to oral and verbal praxis measures; and we found a significant difference between isolated and sequential movements in the oral praxis section in two age subgroups of these groups ( p ≤ .05). Spearman's correlations revealed a strong correlation between core language scores and sequential movements in the younger children with SLI and in TD children. These results showed co-morbidity between SLI and poor oral motor skills, suggesting that SLI is not just a language disorder, but a group of co-morbid conditions that include oral motor and verbal praxis difficulties.